Evaluation Research of Traction Motor Performance for Mine Dump Truck Based on Rough Set Theory - HuiLai Sun; Chun Jin; Shuyang Zheng; Haiyong Tian (Universitas Ahmad Dahlan, 2014)
This paper presents the traction motor evaluation method depending on the electric transmission energy transfer characteristics and different source of supply, including motor manufactures, diesel turbine manufacturers, wheel side reducer manufacturers and electric drive system integrated manufacturers. 9 evaluations are proposed in 3 levels from the motor body and control performance, electric drive system coordinate index, driving conditions and specific cycle. Motor performance evaluation system is published by the means of electric transmission tests and computer simulation platform, using rough set theory. Experimental results show that the model can accurate evaluation of state of the traction motor, Evaluation of the accuracy is better than the subjective weighting analysis, verifying the integrity and usefulness of this valuation method. At the same time, the comprehensive evaluations index of permanent magnet synchronous motors is high, it has important research value.